Antiretroviral treatment failure predicts mortality in rural Tanzania. (August 2015) - Pettersen, Pernille S; Brox, Ida K; Naman, Ezra; Bruun, Johan N; Dyrhol-Riise, Anne M; Trøseid, Marius; Johannessen, Asgeir
Virological monitoring of HIV-infected patients on antiretroviral treatment (ART) is rarely available in resource-limited settings and many patients experience unrecognized virological failure. We studied the long-term consequences of virological failure in rural Tanzania. Previously, virological efficacy was measured in a cohort treated with ART. In the present study, patients with virological failure (VF; HIV-RNA >400 copies/ml) were followed up and compared to those with virological response (VR; HIV-RNA <400 copies/ml) with regard to mortality, CD4 change and subsequent virological outcome. Fifty-six patients with VF had a median CD4 count of 358 cells/µl (interquartile range [IQR] 223–635) and a median HIV-RNA of 13, 573 copies/ml (IQR 2326-129, 736). Median CD4 count for those with VR was 499 cells/µl (IQR 290-636). During a median follow-up time of 39 months (IQR 18-42), 8 of 56 patients (14.3%) with VF died, compared to 1 of 63 patients (1.6%) with VR ( p = 0.009). All registered deaths were HIV-related. Of 55 patients with subsequent HIV-RNA measurements, only 12 of 30 (40%) patients with VF achieved virological suppression, compared to 20 of 25 (80%) patients with VR ( p = 0.003). Virological failure predicted death and subsequent virological failure in patients on ART in a resource-limited setting.